A Sequential Therapeutic Hydrogel With Injectability and Antibacterial Activity for Deep Burn Wounds’ Cleaning and Healing - Wang, Sizhen; Li, Jie; Ma, Zhiqiang; Sun, Linhong; Hou, Lei; Huang, Ying; Zhang, Yunchang; Guo, Beibei; Yang, Feng (Frontiers in Bioengineering and Biotechnology, 2021)
As a severe challenge in clinic, escharectomy and infection are always the core concerns of deep burn injuries. However, a usual dressing without combination of various functions leads to inconvenient treatment on deep burn wounds. Herein we fabricated a sequential therapeutic hydrogel to solve this problem. Crosslinking by modified polyvinyl alcohol (PVA-SH/ε-PL) and benzaldehyde terminated F127 triblock copolymers (PF127-CHO), the hydrogel demonstrated excellent mechanical properties, injectability, tissue adhesiveness, antibacterial activity, biocompatibility and satisfactory wound cleaning through both in vitro and in vivo assays. What’s more, according to a concept of “sequential therapy” we first proposed here, bromelain and EGF are loaded into hydrogel in stages for wound cleaning and healing, respectively. This work provides a strategy to fabricate a kind of promising wound dressing for treatment of deep burn wound, which was verified via deep burn models. The novel hydrogel we designed with satisfactory eschar removing is suitable for irregular shaped wounds because of its injectability, and improves patients’ compliance as it simplified the process of treatment due to its “three in one” characteristic (antibacterial activity, wound cleaning and healing effects), which has great potential in wound dressing development and clinical application.